Automated rubber seed clones identification using reflectance sensors and Arduino: article / Mohammad Nazri Ungor @ Mokhtar - Ungor @ Mokhtar, Mohammad Nazri (2012)
This project presents Automated Rubber Seed Clones Identification by using reflectance sensor (QTR-IA) connected with Arduino. Nowadays, only have three person in Malaysia can compare the type of rubber seed clones. That is means until nowdays, still do not have intelligent device to measure the type of rubber seed clones. So, the main objective of this project is to develop an intelligent technology device that can provide easy way to the user. For this project, there are five types of rubber clones used isRRM***RRIM20l5, RRIM202O, RRIM20Z3and RRIM2(m because it have potential produce high quality product and also familiar in Malaysia. In this project, there three reflectance sensor (QTR-IA) used and also located at different distance. It is because maybe it gives some effect to the result. The device measure the percentage of reflectance based on the intensity of light reflected from the front surface of rubber seed. Result analysis show the average voltage derived from the data and graph constructed, there are small differences of voltage for each type of clones. Finally, the conclusion was made that there are the brightness of brown color at front surface of rubber seed can be used in order to classify the types of rubber tree clones.